How do you prove #(sec(t)+1)(sec(t)-1)=tan^2(t)#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Bdub Share
Mar 8, 2018

Answer:

See Below

Explanation:

#LHS: (sect+1)(sect-1)#

#=sec^2t-1#->FOIL

#=tan^2t+1-1#-> Use the property #sec^2t=tan^2t+1#

#=tan^2t#

#=RHS#

Was this helpful? Let the contributor know!
1500
Impact of this question
74 views around the world
You can reuse this answer
Creative Commons License